Full Scale Test Case For Sailing Yacht Performance - GORMAND, MAËL (My University, 2015)
The present master thesis investigates the possibilities of producing a full scale test case of the performance of sailing yachts. With such a test case, it is believed that instantaneous and absolute performance of sailing yacht evolving in real conditions can be investigated. An out-put of this study is the ability to validate a velocity prediction program with full scale data. Through the use of a sailing yacht, a procedure for performance measurement at sea was developed. This procedure involves the use of on-board electronic instrumentation, displacement measurement and inclining test. A code is developed in Excel c , using VBA c to sort all the data gathered during the measurement campaign. The sorting of data involves the compilation of a database used for plotting the performance of the yacht in two different ways: the first to analyse the instantaneous behaviour of the yacht; the second to analyse the maximum potential performance the yacht can reach. The measurements can then be compared with simulations produced in the “same” sailing condition using a VPP. In this paper, two VPPs are investigated: SailSim c from SSPA AB and WinDesign c from the Wolfson unit at the University of Southampton. The first software has dynamical capabilities but was not used in the end for this research. The second one has only static capabilities and was used for the simulations in the present work. From the comparison between the measurements and the simulations, the quality of full scale data is established and the possibility to validate a VPP using standard sailing electronics is demonstrated. Further development is also suggested and further analysis involving full scale data is proposed. In the present master thesis a universal method to record sailing yacht’s performance data at sea was developed. Then a code to process these data and sort them into a general database useful for further studies was built. It was proven that the quality of nowadays electronics make scientific studies possible. Finally it was demonstrated that standard velocity prediction programs can be validated by full scale data.
Keywords: Farkostteknik; Vehicle Engineering